2010
DOI: 10.1007/s10551-010-0521-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ethical Codes on Ethical Perceptions of Actions Toward Stakeholders

Abstract: ethics codes, ethical attitudes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 73 publications
0
33
0
1
Order By: Relevance
“…In this sense, the inclusion of normative and descriptive components is proposed [131], in such a way that they contribute to redefining business conduct, as well as the principles and values with stakeholders [132]. Thus, it is expected that the effect produced in this research context will promote the study of business ethics not only as a tool for project management but also as an end in itself [133].…”
Section: Ethical Dimensionmentioning
confidence: 99%
“…In this sense, the inclusion of normative and descriptive components is proposed [131], in such a way that they contribute to redefining business conduct, as well as the principles and values with stakeholders [132]. Thus, it is expected that the effect produced in this research context will promote the study of business ethics not only as a tool for project management but also as an end in itself [133].…”
Section: Ethical Dimensionmentioning
confidence: 99%
“…Nevertheless, research has generally suggested that the presence of a code of ethics is positively related to ethical decision making (Loe et al 2000;O'Fallon and Butterfield 2005;e.g. Kaptein 2011;McKinney et al 2010;Pflugrath et al 2007). Thus, the following hypothesis is formulated:…”
Section: Code Of Ethicsmentioning
confidence: 99%
“…It is important for professionals to comply with the codes of ethics of professional bodies to reflect high professionalism. Compliance to ethical codes of conduct by business professionals dictates their unacceptance of unethical behaviour to stakeholders (McKinney, Emerson & Neubert, 2010).…”
Section: Theme 4: Portrayals Of (Men and Women) Professionals In Amentioning
confidence: 99%